Use of Hemoadsorption and Continuous Venovenous Hemodialysis With Enhanced Middle Molecule Clearance in Drug-Induced Rhabdomyolysis - Sebastian Hafner; Johannes Reins; Christoph Baader; Florian Balling; Sebastian Eff (Case Reports in Critical Care)
Drug-induced rhabdomyolysis has become increasingly prevalent due to the rising use of medications such as statins, antidepressants, and antipsychotics. These can lead to muscle cell destruction and the release of myoglobin, potentially causing kidney damage. Recent advancements include the use of CytoSorb hemoadsorption as a promising therapy to remove myoglobin and other potentially toxic substances from the bloodstream. A 47-year-old male with a complex medical history presented with weakness, pain, and dizziness. Lab results indicated severe rhabdomyolysis, most likely of medication-induced etiology. He developed acute kidney injury (AKI) and underwent continuous venovenous hemodialysis (CVVHD) combined with CytoSorb hemoadsorption. Despite initial stabilization, rhabdomyolysis parameters surged, necessitating the use of an additional high-flux filter with enhanced middle molecule clearance. CytoSorb therapy was administered for nine consecutive sessions, resulting in decreased creatine kinase (CK) and myoglobin levels. Due to persistent kidney injury, the patient required permanent dialysis and was transferred to a kidney disease center. This case highlights the complexity and severity of drug-induced rhabdomyolysis with hemoadsorption playing a pivotal role in reducing myoglobin levels and improving the patient’s condition. Combining hemoadsorption and filters with enhanced middle molecule clearance holds even more promise for improved myoglobin removal.